Layered Double Hydroxides Are Promising Nanomaterials for Tissue Bioengineering Application - Jr. da Costa Fernandes, Célio [UNESP]; Pinto, Thaís Silva [UNESP]; Kang, Ha Ram [UNESP]; de Magalhães Padilha, Pedro [UNESP]; Koh, Ivan Hong Jun; Constantino, Vera Regina Leopoldo; Zambuzzi, Willian F. [UNESP] (Wiley, 2019)
Layered double hydroxides (LDHs) have emerged as promising nanomaterials for human health and although it has achieved some progress on this matter, their application within bioengineering is not fully addressed. This prompted to subject fibroblasts to two compositions of LDHs (Mg2Al-Cl and Zn2Al-Cl), considering an acute response. First, LDH particles are addressed by scanning electron microscopy, and no significant effect of the cell culture medium on the shape of LDHs particles is reported although it seems to adsorb some soluble proteins as proposed by energy-dispersive X-ray analysis. These LDHs release magnesium, zinc, and aluminum, but there is no cytotoxic or biocompatibility effects. The data show interference to fibroblast adhesion by driving the reorganization of actin-based cytoskeleton, preliminarily to cell cycle progression. Additionally, these molecular findings are validated by performing a functional wound-healing assay, which is accompanied by a dynamic extracellular matrix remodeling in response to the LDHs. Altogether, the results show that LDHs nanomaterials modulate cell adhesion, proliferation, and migration, delineating new advances on the biomaterial field applied in the context of soft tissue bioengineering, which must be explored in health disorders, such as wound healing in burn injuries.
Keywords: bioengineering; biofabrication; double metal hydroxides; fibroblast; hydrotalcite-like material; layered double hydroxides; nanomaterials